Impact on CO2/N2 and CO2/CH4 Separation Performance Using Cu-BTC with Supported Ionic Liquids-Based Mixed Matrix Membranes - Bernardo Monteiro; Ana R. Nabais; Maria H. Casimiro; Ana P. S. Martins; Rute O. Francisco; Luísa A. Neves; Cláudia C. L. Pereira (Membranes, 2018)
The efficient separation of gases has industrial, economic, and environmental importance. Here, we report the improvement in gas separation performance of a polyimide-based matrix (Matrimid®5218) filled with a Cu-based metal organic framework [MOF, Cu3(BTC)2] with two different ionic liquids (ILs) confined within the pores. The chosen ILs are commonly used in gas solubilization, 1-ethyl-3-methylimidazolium tetrafluoroborate ([EMIM][BF4]) and 1-Ethyl-3-methylimidazolium trifluoromethanesulfonate ([EMIM][OTf]), and the incorporation of the [EMIM][BF4]@Cu-BTC and [EMIM][OTf]@Cu-BTC composites in Matrimid®5218 proved to be an efficient strategy to improve the permeability and selectivity toward CO2/N2 and CO2/CH4 mixtures.